Determination of Aflatoxins in Grains by QuEChERS-UPLC-MS/MS - WU Qin-yan; ZHANG Wen-wen; LIANG Hong-fang; WANG Jian-hua; CHEN Lu (Liang you shipin ke-ji, 2024)
A method based on a QuEChERS sample preparation approach coupled with ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was established to determine six aflatoxins (B1, B2, G1, G2, M1, M2) residues in grains. Samples were extracted with acetonitrile –0.1% formic acid aqueous solution (84 : 16, v/v), followed by purifying with PSA, and determined by UPLC-MS/MS in multiple reaction detection mode with 0.1% formic acid-acetonitrile as mobile phase. The correlation coefficients of the standard curves of the six aflatoxins were all greater than 0.99, showing good linearity. The recoveries were 80.83%~117.5%, and the relative standard deviations (RSD) were 1.53%~15.59%. The matrix effects of six aflatoxins were 0.81~1.12 in different varieties of grains. The accuracy and precision of this method meet the requirements of relevant standards, and have the advantages of simple pretreatment technology, good purification effect and high precision determination, which could be suitable for the quantitative analysis of six aflatoxins in wheat, rice, corn, mung bean and red bean samples.